1984
DOI: 10.2190/yc8t-hk4h-809b-cegu
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Evaluation of a Channel One Program

Abstract: The purpose of this evaluation was to determine the effectiveness and cost-effectiveness of an alternatives program entitled Channel One. The evaluation design included the collection of process and outcome data. Results of the process evaluation indicated that the program was operating consistently with the philosophy and procedures of Channel One. The outcome data indicated significant improvement in democratic patterns and alternative participation, but also indicated increased use of some substances and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although school systems and social agencies invest a large share of their prevention resources in Alternatives programs, there is very little published evidence of their effectiveness as deterrents of substance use (Kim, 1981;Moskowitz et al, 1983Moskowitz et al, , 1984Cook et al, 1984;Stein et al, 1984). One study suggested that Alternatives programs with skills acquisition components and a large number of hours of programming, could be effective with "high-risk" youth (Tobler, 1986).…”
Section: Alternatives Modelmentioning
confidence: 99%
“…Although school systems and social agencies invest a large share of their prevention resources in Alternatives programs, there is very little published evidence of their effectiveness as deterrents of substance use (Kim, 1981;Moskowitz et al, 1983Moskowitz et al, , 1984Cook et al, 1984;Stein et al, 1984). One study suggested that Alternatives programs with skills acquisition components and a large number of hours of programming, could be effective with "high-risk" youth (Tobler, 1986).…”
Section: Alternatives Modelmentioning
confidence: 99%
“…Community interventions create activities to replace or supercede substance use (Cullen, 1982;Johnson &Solis, 1983;Kim, 1983). An example is Channel One, a nationwide program to prevent adolescent drug abuse via alternative recreations and local projects (Stein, Swisher, Hu, & McDonnell, 1984). Involving nearly 3,800 young persons, the program demonstrates the scope of community interventions.…”
Section: Environmentmentioning
confidence: 99%